Antimycobacterial effect of plant derived phthalate against Mycobacterium tuberculosis H37Ra. (January 2022) - Priyadarshini, Nivedita; Veeramani, Aranganathan; Chinnathambi, Pothiraj; Palanichamy, Ayyappan; Al-Dosary, Munirah Abdullah; Ali, Mohammad Ajmal; Lee, Joongku; Paulraj, Balaji
Abstract: Plants serve as primary source of medication and have also proved to be effective against innumerable pathogens. Ethnobotanical plants Tithonia diversifolia (Hemsl.) A. Gray and Couroupita guianensis Aubl ., were considered for this study against Mycobacterium tuberculosis (MTB). The two purified and isolated components Zingiberene (ZGB) and Bis 2- (ethyl hexyl) phthalate (BEHP) from both plant leaves were tested for their drug susceptibility, synergy and in silico molecular docking against MTB H37Ra. At a concentration of 60 g/mL, the microorganism showed drug sensitivity to BEHP, whereas ZGB was futile. Synergy studies of the components showed fractional inhibitory concentration indices exhibiting an overall additive effect. Meanwhile the docking studies, BEHP-inhA gene complex alone gave the lowest binding energy of −7.31 Kcal/mol when docked with potential drug target genes of MTB H37Ra. Therefore, plant-derived BEHP can be considered as a potent antimycobacterial component. Highlights: The study includes antimycobacterial synergy, drug susceptibility, and mode of action. Potent components, zingiberene and bis 2- (ethyl hexyl) phthalate was isolated. The overall synergy index and drug susceptibility proved tuberculosis sensitive. In silico and ADME studies validated the potentiality of mycobacterial strain H37Ra.